Potential regulatory implications of Health Canada's new lead guideline. Issue 4 (24th August 2020) - Locsin, Javier M.; Trueman, Benjamin F.; Serracin‐Pitti, Dallys; Stanton, Gillian M. L.; Gagnon, Graham A.
Abstract: Health Canada's guideline for lead in drinking water was updated in March 2019. Two new sampling protocols were introduced—random daytime and 30‐min stagnation sampling—and the maximum acceptable concentration (MAC) of lead in drinking water was decreased from 10 to 5 μg/L. This study examined the possible impacts that changes in the guideline might have on water utilities in Canada. A lead‐monitoring survey of seven drinking water distribution systems was conducted using the random daytime and 30‐min stagnation protocols. Random daytime sampling captured an estimated 45% more lead than 30‐min stagnation sampling. However, both protocols yielded samples above the new MAC: 7.5% and 5.4% of random daytime and 30‐min stagnation samples, respectively, exceeded it. These data indicate that some drinking water providers—especially those supplying systems with legacy lead plumbing—may have difficulty achieving 100% compliance with the new guideline.